Medical Computing Visual Synchronization Using WebSocket Protocol and Web Rendering - Zhang, Qi (Conference proceedings - Canadian Conference on Electrical and Computer Engineering, 2019)
Web based 3D medical data computing and visual synchronization can provide clinical users with critical information for distributed diagnosis and treatment. However, due to the limited internet bandwidth, high computational cost and increasing data size, real-time medical data exploration and information sharing on internet is still a challenging task. Therefore, we developed a new internet based medical data computing and information visual distribution system, in which graphics processing units were utilized for parallel medical data computing and visualization, cloud was used for data storage, Apache HTTP Server and MySQL were employed for medical image management and analysis, and WebSocket Protocol was used for medical information visual synchronization. The major contributions include algorithms developed for high performance medical computing, and medical information sharing and visual synchronization on distributed web browsers. The developed system can provide medical users with intuitive feedback for collaborative diagnosis and remote therapy.